A protocol for irradiation of cell lines cultured in multi-well plates: effect of air inhomogeneity on irradiated cell survival. (2nd November 2019) - Mahdavi, Bibi Fatemeh; Taheri, Azade; Hejazi, Seyed Hossein; Talebi, Ardeshir; Shokrani, Parvaneh
Abstract: Introduction : In multi-well cell culture plates, wells are bordered by air cavities. The air cavity inhomogeneities can reduce the amount of delivered dose. In this study, the effect of these cavities on cell survival was investigated. Materials and methods : A special phantom was designed to house the plates and air cavities were filled by water equivalent materials. Cultured melanoma cells were irradiated using 6MV photon for 200 cGy. MTT and clonogenic assay tests were used to evaluate cell survival. Results : Results of MTT assay showed mean survival percentage for irradiated cells in the first group, i.e. plates with air cavities, was 18.9% higher than the second group with air cavities filled with paraffin. Clonogenic assay results showed a maximum of 37% difference in the mean of number of colonies between the first group and the second group ( p value < .05). Conclusions : The presence of air cavities in multi-well cell culture plates reduced radiation cell kill by up to 37%. To ensure the accuracy of delivered dose, it is necessary to replace the air cavities as well as the air surrounding the plates by a water equivalent material.